"Security and growth for all in the Indian Ocean" – maritime governance and India's foreign policy. Issue 5 (20th October 2019) - Schöttli, Jivanta
ABSTRACT: In a March 2015 speech delivered in Mauritius, India's current Prime Minister Narendra Modi outlined what he described would be India's vision for the Indian Ocean Region. Under the acronym, SAGAR or "Security and Growth for All in the Region, " five key points were elucidated. At the time, the speech was praised for articulating a proactive approach to the Indian Ocean and the various visits to, and agreements that followed with, littoral and island countries, appeared to confirm this. This paper seeks to assess the extent to which India has been able to deliver an agenda of security and growth for the maritime region. Despite the enthusiastic reception to SAGAR, the critique is often made that India is slow to deliver on the promises made as part of the country's maritime and naval diplomacy. The paper highlights a selection of decisions and actions taken since 2015, which have contributed to maritime governance in the region and argues that there is a substantial change in the way SAGAR provides a framework for strategic action.